EFEKTIFITAS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KATA PADA ANAK KESULITAN BELAJAR KELAS III di SDN 15 ULU GADUT - FITRIA HERMAN (Universitas Negeri Padang, 2015)
This research in the wake of the problems that researchers have found in SD N 15 Ulu Gadut Padang, a third grade children learning disability who are having problems in reading the word. The ability to read the children is still very low, children are often wrong in reading the words contained digraphs letters